Managing preservation for libraries and archives (Ashgate, 2004)
The book offers guidelines on how to safely store materials that include paper, digital information, and sound recordings. Digital preservation and management are described in three separate chapters that has contributed an introduction outlining preservation principles and policies. The book also describes future trends and offers a lengthy chapter on the sources of information for digital preservation management